Secondary School Students’ Environmental Concerns: a Case Study from Slovenia - Torkar, Gregor (Uniwersytet Rzeszowski: Południowo-Wschodni Oddział Polskiego Towarzystwa Inżynierii Ekologicznej z siedzibą w Rzeszowie, 2016)
Students’ environmental concerns were investigated using a questionnaire with 12 items. The study sample comprised 410 first and second year students of general upper secondary school from NW Slovenia. Results provide evidence that students’ concerns for the consequences of environmental damage formed three correlated factors organized around self and family, all people, and the biosphere. The highest was students’ environmental concern for the biosphere, followed by concern for self and family, and concern for all the people. Gender differences were significant in concerns for all people and for the biosphere; female students were more concerned than male students. Age differences were significant in concerns for the biosphere in favour of older students. Since humanity is facing challenges in balancing our demands and ecological limitations, the results of this study could be beneficial for further development of environmental education.

Do zbadania niepokojów uczniów wywołanych stanem środowiska użyto kwestionariusza złożonego z dwunastu elementów. Próba badawcza składała się z 410 uczniów pierwszej i drugiej klasy liceum ogólnokształcącego z północno- zachodniej Slowenii. Wyniki wskazują na to, że zaniepokojenie uczniów konsekwencjami niszczenia środowiska oscylują wokół trzech skorelowanych czynników dotyczących siebie i rodziny, wszystkich ludzi i biosfery. Młodzi ludzie wykazali najwyższy poziom zaniepokojenia stanem biosfery, potem sobą i rodzina, na końcu troską o wszystkich ludzi. Wśród kobiet i mężczyzn różnice były istotne jeśli chodzi o wszystkich ludzi i biosferę; kobiety wykazały większe zaniepokojenie tymi aspektami niż mężczyźni. Jeśli chodzi o wiek respondentów, starsi uczniowie byli bardziej zaniepokojeni stanem biosfery niż młodsi. Z uwagi na to, że ludzkość stoi przed wyzwaniami związanymi z dążeniem do równowagi pomiędzy chęcią zaspokajania naszych potrzeb, a ograniczeniami ekologicznymi, wyniki tego badania mogłyby mieć korzystny wpływ na dalszy rozwój edukacji pro- środowiskowej.
Keywords: environmental concern; secondary school; students; gender; age; Slovenia; niepokój wywołany stanem środowiska; uczniowie liceum; płeć; wiek; Słowenia